Integrating multiple stubs in stepped‐impedance filter aiming for high selectivity. Issue 14 (24th May 2022) - Sami, Abdul; Gomez Laso, Miguel Angel; Lopetegi, Txema; Arnedo, Israel; Calero, Ibai; Teberio, Fernando; Martin Iglesias, Petronilo; Benito, David; Arregui, Ivan
Abstract: A design technique to include multiple and fully‐controlled transmission zeros (TZs) in the frequency response of rectangular waveguide commensurate‐line stepped‐impedance filters is presented in this letter. These bandpass filters (BPFs) are known for having reduced sensitivities against manufacturing inaccuracies and are composed of multiple waveguide sections. In order to improve their selectivity, 3λ g /4 and λ g /4‐stubs are included to create multiple TZs around the passband. The proposed technique allows us to add multiple stubs in a single section and, therefore, only minor adjustments in the affected part of the filter are required, which simplifies the overall design process. The technique has been verified with a design example with four TZs (two on each side) near the passband.